Manufacturing Consent for the 2018 Elections in Venezuela and Colombia - Alan MacLeod (Media Theory, 2018)
Herman and Chomsky laid out their propaganda model of how foreign countries are presented in the news directly relates to their closeness with Washington. Criticisms of the model declare it overly deterministic and lacking in evidence for the everyday functions of journalism. This article assesses Western media coverage of the Colombian and Venezuelan elections of 2018, finding that the propaganda model continues to hold. Furthermore, by conducting a series of 27 interviews with journalists covering the two countries, it finds evidence to support Herman and Chomsky’s theories about the pre-selection of journalists and how ownership and management, sources and flak influence the output of media.